CHILDHOOD OBESITY AND ITS IMPACT ON HEALTH (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis scientifically analyzes the problem of obesity in children, its causes, health effects, as well as prevention and treatment methods. The research results show that obesity is related to improper nutrition, physical inactivity, and hormonal disorders. It also emphasizes that obesity can lead to serious consequences such as cardiovascular diseases, diabetes, and psychological issues. The thesis highlights the importance of proper nutrition, increased physical activity, and psychological support in preventing obesity. Practical recommendations for improving children’s health and preventing obesity are provided in this work.